Phytobiotics with Adsorbent to Mitigate Toxicity of Multiple Mycotoxins on Health and Growth of Pigs - Debora Muratori Holanda; Young Ihn Kim; Wanpuech Parnsen; Sung Woo Kim (Toxins, 2021)
Phytobiotics with a mycotoxin adsorbent were used to mitigate negative effects of multiple mycotoxins in diets fed to pigs. In experiment 1, 120 pigs (11.6 kg body weight; BW) were assigned to five treatments (three pigs/pen) and fed for 28 days. Treatments were CON (control), MTD (CON + 2.5 mg/kg of deoxynivalenol), DP (MTD + phytobiotics at 0.1%), and DPA1 and DPA2 (MTD + phytobiotics and adsorbent at 0.1% and 0.2%, respectively). In experiment 2, 96 pigs (28.5 kg BW) were assigned to four treatments (three pigs/pen) and fed for 26 days. Treatments were CON, MTAF (CON + 0.19 mg/kg of aflatoxin and 8 mg/kg of fumonisins), AFP (MTAF + phytobiotics at 0.1%), and AFPA (MTAF + phytobiotics and adsorbent at 0.1%). Growth performance was measured weekly, and blood was sampled at the end of study to measure hepatic function and inflammatory status (TNF-α). Data were analyzed using the MIXED procedure. In experiment 1, pigs fed MTD, DP, DPA1, and DPA2 had smaller (p < 0.05) BW than CON. Pigs fed DPA2 had greater (p < 0.05) BW than MTD. Pigs fed DP and DPA2 tended to have lower (p < 0.1) serum total protein than CON. Pigs fed MTD and DPA2 tended to have higher (p < 0.1) alanine aminotransferase than CON. Similarly, pigs fed MTD, DP, and DPA2 tended to have higher (p < 0.1) urea nitrogen/creatinine than CON. In experiment 2, pigs fed MTAF, AFP, and AFPA had smaller (p < 0.05) BW than CON. Pigs fed MTAF, AFP, and AFPA had smaller (p < 0.05) ADFI than CON. Pigs fed AFPA had higher (p < 0.05) aspartate aminotransferase than CON and MTAF. Pigs fed AFP and AFPA had higher (p < 0.05) alanine aminotransferase than CON. Pigs fed MTAF, AFP, and AFPA had lower (p < 0.05) urea nitrogen/creatinine than CON. Pigs fed AFPA had higher (p < 0.05) TNF-α than CON and MTAF. In conclusion, feeding an additional 2.5 mg/kg of deoxynivalenol or 0.19 mg/kg of aflatoxin with 8 mg/kg of fumonisins reduced the growth of pigs. Deoxynivalenol compromised the hepatic function of pigs. Phytobiotics with adsorbent could partly overcome the detrimental effects of mycotoxins.